GRN−/− iPSC-derived cortical neurons recapitulate the pathological findings of both frontotemporal lobar degeneration and neuronal ceroidolipofuscinosis - Patrizia Bossolasco; Sara Cimini; Emanuela Maderna; Donatella Bardelli; Laura Canafoglia; Tiziana Cavallaro; Martina Ricci; Vincenzo Silani; Gianluca Marucci; Giacomina Rossi (Neurobiology of Disease, 2022)
Heterozygous mutations in the gene coding for progranulin (GRN) cause frontotemporal lobar degeneration (FTLD) while homozygous mutations are linked to neuronal ceroidolipofuscinosis (NCL). While both FTLD/NCL pathological hallmarks were mostly investigated in heterozygous GRN+/− brain tissue or induced pluripotent stem cell (iPSC)-derived neurons, data from homozygous GRN−/− condition are scarce, being limited to a postmortem brain tissue from a single case. Indeed, homozygous GRN−/− is an extremely rare condition reported in very few cases. Our aim was to investigate pathological phenotypes associated with FTLD and NCL in iPSC-derived cortical neurons from a GRN−/− patient affected by NCL. iPSCs were generated from peripheral blood of a GRN wt healthy donor and a GRN−/− patient and subsequently differentiated into cortical neurons. Several pathological changes were investigated, by means of immunocytochemical, biochemical and ultrastructural analyses. GRN−/− patient-derived cortical neurons displayed both TDP-43 and phospho-TDP-43 mislocalization, enlarged autofluorescent lysosomes and electron-dense vesicles containing storage material with granular, curvilinear and fingerprints profiles. In addition, different patterns in the expression of TDP-43, caspase 3 and cleaved caspase 3 were observed by biochemical analysis at different time points of cortical differentiation. At variance with previous findings, the present data highlight the existence of both FTLD- and NCL-linked pathological features in GRN−/− iPSC-derived cortical neurons from a NCL patient. They also suggest an evolution in the appearance of these features: firstly, FTLD-related TDP-43 alterations and initial NCL storage materials were detected; afterwards, mainly well-shaped NCL storage materials were present, while some FTLD features were not observed anymore.